Dificuldades e possibilidades para o ensino de Botânica na cidade de Altamira-PA - FIGUEREDO, Francisco Alex Oliveira (2023)
This course conclusion work presents the results of a research with a qualitative approach, developed in 2019, with the goals of: (1) knowing the opinions of Science/Biology teachers about obstacles and possibilities for the teaching of Botany; (2) analyzing the possibilities for the Science/Biology teacher to build a school herbarium as an attractive methodological strategy for the teaching of Botany, with the participation of the students as protagonists. The research collected data through contact with two groups of subjects: 1. Science and Biology teachers who work in public schools in the city of Altamira-PA; 2. High school students from one of these teachers’ schools. As techniques and instruments for data collectin, the researchers used interviews with smi-structured script with teachers and direct observation and conversation with students. Among the results achieved, it is highlighted that the greatest obstacle for the teaching of Botany in these schools is strongly related to the lack of didactic materials for more attractive practical classes that are easily accessible to teachers. Thus, we also emphasize that the production of a school herbarium can be a viable possibility to face this problem/obstacle.